Exploration of Traditional Game of Marbles in Maths Learning in Primary School - Elsi Oktarina (Institut Agama Islam Negeri Palopo, 2022)
Exploration a mathematical concept found in a culture. the presence of culture nuancedmathematics will make a major contribution to the learning of mathematics. The purpose ofthis study is to identify and describe mathematical objects found in the traditional display ofmarbles and their use in learning mathematics. This research is a qualitative research using ethnographic methods. The instruments used in this study were documentation, interviews andliterature studies directly to respondents. Data analysis techniques are performed by datareduction, data presentation and data analysis and data exposure. The results of the study indicate that traditional marbles games have ethnomatematics related to mathematical concepts including geometrical concepts such as circles, spheres, triangles and also the concept of distance. The mathematical concepts can be used to introduce and understand the concept of geometry and distance through local culture.